Study of Antigen Expression by Human Neurocells of Different Gestation Term during Culturing In Vitro - Lisyanyy, M. I.; Lyubich, L. D.; Semenova, V. M.; Stayno, L. P.; Vysotskiy, M. S.; Potapova, A. I. (Problems of Cryobiology and Cryomedicine, 2008)
The HLA expression by human neurocells (NC) of different gestation term and differentiation on the protein and mRNA levels using methods of immunophenotyping and RT-PCR has been studied. Under culturing human NC of 5–6 week’ gestation term in DMEM + retinol acetate the amount and percentage of HLA I and II expressing cells on the protein and mRNA levels were decreased whereas the presence in the culturing medium of the growth factors contributed to preservation (FGF) or increasing (EGF) of positive expressing cells amount. Under culturing in DMEM the HLA I and II expressing Bulbus olfactorius cells number decreased from day 10th to 20th.